Do common infections trigger disease-onset or -severity in CTLA-4 insufficiency? - Krausz, Máté; Mitsuiki, Noriko; Falcone, Valeria; Komp, Johanna; Posadas-Cantera, Sara; Lorenz, Hanns-Martin; Litzman, Jiri; Wolff, Daniel; Kanariou, Maria; Heinkele, Anita; Speckmann, Carsten; Häcker, Georg; et al. (Frontiers in Immunology, 2022)
Purpose: Heterozygous mutations in CTLA4 lead to an inborn error of immunity characterized by immune dysregulation and immunodeficiency, known as CTLA-4 insufficiency. Cohort studies on CTLA4 mutation carriers showed a reduced penetrance (around 70%) and variable disease expressivity, suggesting the presence of modifying factors. It is well studied that infections can trigger autoimmunity in humans, especially in combination with a genetic predisposition. Methods: To investigate whether specific infections or the presence of specific persisting pathogens are associated with disease onset or severity in CTLA-4 insufficiency, we have examined the humoral immune response in 13 CTLA4 mutation carriers, seven without clinical manifestation and six with autoimmune manifestations, but without immunoglobulin replacement therapy against cytomegalovirus (CMV), Epstein-Barr virus (EBV), herpes simplex virus 1/2 (HSV 1/2), parvovirus B19 and Toxoplasma gondii. Additionally, we have measured FcγRIII/CD16A activation by EBV-specific IgG antibodies to examine the functional capabilities of immunoglobulins produced by CTLA4 mutation carriers. Results: The seroprevalence between affected and unaffected CTLA4 mutation carriers did not differ significantly for the examined pathogens. Additionally, we show here that CTLA4 mutation carriers produce EBV-specific IgG, which are unimpaired in activating FcγRIII/CD16A. Conclusions: Our results show that the investigated pathogens are very unlikely to trigger the disease onset in CTLA-4-insufficient individuals, and their prevalence is not correlated with disease severity or expressivity.